SECONDARY ANTIBODY TITER RESPONSE IN PIGS FOLLOWING STREPTOCOCCUS SUIS VACCINATION WITH VARIOUS ADJUVANTS: DETECTION USING SUPERNATANT ANTIGEN-BASED ELISA - Gede Gita Pratama; I Nengah Kerta Besung; Hapsari Mahatmi; I Gusti Ngurah Kade Mahardika; Ni Ketut Suwiti (Buletin Veteriner Udayana, 2025)
Streptococcus suis is a pathogenic bacterium that causes severe disease in pigs and poses a zoonotic risk to humans. Vaccination is one of the primary preventive strategies, and its effectiveness can be enhanced through the use of appropriate adjuvants. This study aimed to evaluate the secondary humoral immune response in pigs vaccinated with a locally derived S. suis vaccine formulated with two different adjuvants: Montanide ISA 201 VG and Montanide Gel-01. In addition, the study observed the dynamics of antibody titters over time post-vaccination. Twelve pigs were divided into three treatment groups: a control group (unvaccinated), a group vaccinated with Montanide ISA 201 VG, and a group vaccinated with Montanide Gel-01. Blood samples were collected weekly for five weeks following the booster vaccination, and antibody titers were measured using ELISA based on culture supernatant antigens. Data were analyzed using analysis of variance and linear regression. The results showed that both adjuvants significantly increased antibody titers compared to the control (p < 0.05), with Montanide Gel-01 producing the highest titer (0.718 ± 0.0397), followed by ISA 201 VG (0.703 ± 0.0320), and the control group (0.459 ± 0.0419). Furthermore, the timing of serum collection significantly influenced antibody titer levels (p < 0.005). This study concludes that the use of Montanide adjuvants, particularly Gel-01, is effective in enhancing the humoral immune response to S. suis vaccination. Further research is recommended to evaluate the effects of increasing antigen concentration for achieving a more robust immune response.